2014
DOI: 10.1107/s1600577514003014
|View full text |Cite
|
Sign up to set email alerts
|

Development of a bent Laue beam-expanding double-crystal monochromator for biomedical X-ray imaging

Abstract: A bent Laue beam-expanding double-crystal monochromator was developed and tested at the Biomedical Imaging and Therapy beamline at the Canadian Light Source. The expander will reduce scanning time for micro-computed tomography and allow dynamic imaging that has not previously been possible at this beamline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Previous results (Martinson et al, 2014) reported a vertical beam expansion of approximately 7.7Â. During these experiments, we discovered that the beam expander destroyed the phase characteristics of the beam in the vertical direction (corresponding to horizontal edges in the object) and caused blurring of horizontal (but not vertical) knife-edges placed at longer sample-to-detector distances.…”
Section: Introductionmentioning
confidence: 59%
“…Previous results (Martinson et al, 2014) reported a vertical beam expansion of approximately 7.7Â. During these experiments, we discovered that the beam expander destroyed the phase characteristics of the beam in the vertical direction (corresponding to horizontal edges in the object) and caused blurring of horizontal (but not vertical) knife-edges placed at longer sample-to-detector distances.…”
Section: Introductionmentioning
confidence: 59%
“…While ideal matching may be required for certain microfocusing applications of bent Laue double-crystal monochromators, it would appear that, as long as both crystals are in the upper sign geometry [i.e. the tilt angle of crystal is + B instead of the À B tilt that is now believed to be the primary cause of the beam blurring observed in our earlier work (Martinson et al, 2014)], the system will produce a suitable beam for biomedical imaging with phase contrast techniques. …”
Section: Resultsmentioning
confidence: 98%
“…The beam-expanding system was set up as shown by Martinson et al (2014) with the geometric focus of the second crystal matched to that of the first crystal. The bend radii of the first and second crystals were 0.5 m and 5 m, respectively, producing an expansion factor of approximately 10, with a crystal-to-crystal distance of approximately 2 m. Using a Hamamatsu detector [AA-60 beam monitor coupled to a C9300-124 CCD camera resulting in a field of view of 31.08 mm (H) Â 23.31 mm (V) and pixel size 8.75 mm] and object-to-detector distance of 134 cm, images of a knife-edge (tungsten bar) and phase object (Lucite rod) were captured through Bragg angles ranging AE 1 from the magic condition (see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Making full use of the large animal imaging stage, a feature unique to this facility (Wysokinski et al, 2007), similarly requires a larger field of view. Previous results (Martinson et al, 2014(Martinson et al, , 2015 reported on the development of a phase-preserving bent Laue beamexpanding double-crystal monochromator: two silicon (Si) crystal wafers were cylindrically bent with the concave sides facing the X-ray beam and arranged with the geometrical foci of both crystals co-located and the diffraction planes parallel ISSN 1600-5775 between each crystal as in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%